Occurrence of Avian Mycoplasmas in Free-Living Muscovy-Ducks (Cairina Moschata) - BSN Magalhães; VLA Pereira; LS Machado; TS Dias; DA Balthazar; ML Barreto; F Troccoli; NC Cunha; ER Nascimento; FM Almeida; NR Almosny (Brazilian Journal of Poultry Science, 2020)
ABSTRACT The present study aimed to investigate, by culture and PCR, the occurrence of Mollicutes, Mycoplasma gallisepticum and Mycoplasma synoviae in free-living Muscovy-ducks (Cairina moschata) from the Rio Zoo, RJ, Brazil. Tracheal swabs were obtained from 82 asymptomatic ducks and the samples were submitted to culture of mycoplasmas and PCR for identification of Mollicutes Class, Mycoplasma gallisepticum (MG) and Mycoplasma synoviae (MS). Samples were also analyzed directly by PCR, without prior culture, for Mollicutes, MG and MS. Eighteen (18/82) Muscovy-ducks were positive for Mollicutes by culture, all isolates were confirmed as Mollicutes and seven were identified as MG. Of the samples analyzed directly by PCR, without prior culture, 17,1% (14/82) was positive for Mollicutes, being 35,7% (5/14) identified as MG and 21,4% (3/14) as MS. The occurrence of Mollicutes class bacteria was detected in Muscovy-ducks. MG and MS were identified in these animals suggesting the circulation of these agents in the Rio de Janeiro Zoo and may present a risk for the health status of the other birds.